“FQ em rede” and “e-lab” openning the school laboratories - Monteiro, Vera (2011)
This paper is a reflection on the potential of learning communities in the Web 2.0 in terms of learning (formal and informal) for young people. Specifically, it focuses on the integration of real remote laboratories like “e-lab.ist.eu” in the community of students and teachers of secondary education - "FQ em rede" and how it can expand and flatten the school frontiers, in particular those of laboratories. It generates new opportunities for involvement and new learning around the experimental activities provided by the remotely controlled laboratories, such as "e-lab".